2023
DOI: 10.22460/infinity.v12i1.p69-84
|View full text |Cite
|
Sign up to set email alerts
|

Developing Realistic Mathematics Education-Based Worksheets for Improving Students’ Critical Thinking Skills

Abstract: Applying critical thinking is an essential skill in the 21st century. However, teaching materials that do not facilitate students to improve these skills impact the achievement of learning objectives. Therefore, educators need appropriate teaching materials that encourage students to enhance their thinking skills. This study aims to develop teaching materials based on Realistic Mathematics Education (RME) to improve students’ critical thinking skills. The development model used is ADDIE consisting of Analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Learning using student worksheets that are based on real-world contexts and accompanied by activities to use visual aids is very suitable for improving students' mathematical thinking skills (Hirza & Kusumah, 2014). In line with this, Lestari et al (2023) also found that realistic learning utilizing worksheets is practical and effective in improving students' critical thinking skills in mathematics lessons.…”
Section: What-if Questionmentioning
confidence: 59%
“…Learning using student worksheets that are based on real-world contexts and accompanied by activities to use visual aids is very suitable for improving students' mathematical thinking skills (Hirza & Kusumah, 2014). In line with this, Lestari et al (2023) also found that realistic learning utilizing worksheets is practical and effective in improving students' critical thinking skills in mathematics lessons.…”
Section: What-if Questionmentioning
confidence: 59%
“…The current learning situation in schools shows a challenge in developing critical thinking skills in learners (Fadhilah et al, 2022;Lestari et al, 2023;Ximenes et al, 2023). Classroom observations and evaluation of learning outcomes show that many learners demonstrate low critical thinking skills.…”
Section: Discussionmentioning
confidence: 99%
“…The skill is useful to obtain, manage, and utilize the received information. Students need critical thinking skills to implement various methods of solving problems (Syawaludin et al, 2019;Lestari et al, 2023). Therefore, critical thinking skills are important to apply in learning activities at every level of education.…”
Section: Introductionmentioning
confidence: 99%